Timing of antipsychotics and benzodiazepine initiation during a first episode of psychosis impacts clinical outcomes: Electronic health record cohort study - Arribas, Maite; Solmi, Marco; Thompson, Trevor; Oliver, Dominic; Fusar-Poli, Paolo (Frontiers in Psychiatry, 2022)
The impact of timing of antipsychotics and benzodiazepine treatment during a first episode of psychosis on clinical outcomes is unknown. We present a RECORD-compliant electronic health record cohort study including patients (n=4,483, aged 14-35) with a primary diagnosis of any nonorganic ICD-10 first episode of psychosis at SLAM-NHS between 2007 and 2017. The impact of antipsychotic timing (prescription>1 week after a first episode of psychosis) was assessed on the primary outcome (risk of any psychiatric inpatient admission over 6 years), and secondary outcomes (cumulative duration of any psychiatric/medical/accident/emergency[A&E] admission over 6 years). The impact of prescribing benzodiazepine before antipsychotic at any point and of treatment patterns (antipsychotic alone, benzodiazepine alone, combination of antipsychotic with benzodiazepine) within the first week after a first episode of psychosis were also assessed. Survival analyses and zero-inflated negative binomial regressions, adjusted for core covariates, and complementary analyses were employed. Antipsychotic prescribed>1 week after a first episode of psychosis did not affect the risk of any psychiatric admission (HR=1.04, 95%CI 0.92-1.17, p=0.557), but increased the duration of any psychiatric (22%-28%), medical (78%-35%) and A&E (30%-34%) admission (months 12-72). Prescribing benzodiazepine before antipsychotic at any point did not affect the risk of any psychiatric admission (HR=1.03, 95%CI 0.94-1.13, p=0.535), but reduced the duration of any psychiatric admission (17%-24%, months 12-72), and increased the duration of medical (71%-45%, months 12-72) and A&E (26%-18%, months 12-36) admission. Prescribing antipsychotic combined with benzodiazepine within the first week after a first episode of psychosis showed better overall clinical outcomes than antipsychotic or benzodiazepine alone. Overall, delaying antipsychotic 1 week after a first episode of psychosis may worsen some clinical outcomes. Early benzodiazepine treatment can be considered with concomitant antipsychotic but not as standalone intervention.